2022
DOI: 10.1177/14034948221075025
|View full text |Cite
|
Sign up to set email alerts
|

Increases in drug overdose deaths in Norway and the United States during the COVID-19 pandemic

Abstract: Introduction: Little international comparative work exists describing pandemic-related spikes in overdose and related implications for drug and public health policy. We compared increases in overdose deaths during the pandemic in Norway and the United States, two countries in the top 10 for per-capita overdose mortality, yet with very different approaches to the pandemic, healthcare and drug policy. Methods: We examined monthly overdoses in 2020 versus baseline rates (the monthly average across 2017–2019). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
1
Order By: Relevance
“…Unregulated drug poisoning (overdose) is a public health emergency in North America and internationally that worsened during the covid-19 pandemic. 1 2 Since March 2020, overdose related mortality has increased in Canada and the United States, where 7560 and 80 816 people respectively died of overdose in 2021. 3 4 5 Adulteration of the illegal drug supply with fentanyl is the leading contributor to overdose related deaths in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Unregulated drug poisoning (overdose) is a public health emergency in North America and internationally that worsened during the covid-19 pandemic. 1 2 Since March 2020, overdose related mortality has increased in Canada and the United States, where 7560 and 80 816 people respectively died of overdose in 2021. 3 4 5 Adulteration of the illegal drug supply with fentanyl is the leading contributor to overdose related deaths in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The present study only includes all-cause mortality, being unable to identify drug-related deaths. Other studies, however, have found evidence of this increase [28], and persons with SUD/MI are reported to have consumed stronger substances than usual to cope with the pandemic [21]. With restricted access to syringe services, persons who inject drugs might have re-used or shared syringes, which could have caused infections.…”
Section: ***Please Insert Table 1 Here*** Sars-cov-2 Infectionmentioning
confidence: 99%
“…Det er det høyeste antall overdoser registrert på 20 år. Overdoser økte kraftig i Norge under pandemien, antageligvis på grunn av sterkere heroin på markedet og begrenset tilgang til lavterskeltilbud, men tallene har nå stabilisert seg ( Friedman & Gjersing, 2022 ). De alle fleste overdosetilfeller i Norge skyldes opioider, hvorav illegal heroin er hovedårsaken (FHI, 2021).…”
Section: Bakgrunnunclassified